Implementation of Strategic Planning in Regional/ Municipal Governments, Obstacles and Challenges - Nunuk Dwi Retnandari (Indonesian Association for Public Administration, 2022)
This article discusses strategic planning implementation of the public sector within Indonesia’s hierarchical administration system. Many studies on public sector strategic planning have been carried out both at the national and local levels. However, the disclosure of various obstacles and challenges in the implementation of strategic planning at the local level is still partial and sectoral. A qualitative strategy was used to explain this phenomenon with participatory observation in 69 regency/municipalities as the main data collection method, in addition to document analysis and in-depth interviews. The key findings from this article are that many strategic planning documents are a mere formality, are not strategic, and are not referred to in executing development activities. The challenges in strategic planning implementation were identified as being poor information and data quality and quantity, weak bargaining position that regencies/municipalities have against higher tiered administration, limited capacity of mid-level managers, limited capacity of planners, formal engagement of stakeholders, and unconducive political environment. Improvement of the evaluation model based on the achievement of outcomes, reducing the ministry's sectoral ego, improving the capacity of evaluators and the need for the involvement of other parties such as credible universities will create a multiplier effect for all stakeholders.